O botânico Henrique Lahmeyer de Mello Barreto e sua contribuição para o conhecimento da flora de Minas Gerais - Gustavo Santos Silva (2018)
The history of botany in Brazil in the first half of the 20th century is little known, but very important, since it was when diverse institutions, such as universities and research centers, began to spread and consolidate, driven by scientific and technological advances and new challenges political, social and economic. To support research in the botanic area, some herbaria were created at that time and now house samples of plants collected in environments that no longer exist or are altered. In this context, the collection left by the researcher Henrique Lamayer de Mello Barreto, with plants collected in Minas Gerais in the 1930s and 1940s, can be considered one of the most important. Their samples were distributed to several national and foreign herbaria and served as a basis for description of numerous new species for science. Despite this, little is known about his career, his work and the effective contribution given to the knowledge of the flora of Minas Gerais. The objectives of this work were to retrieve information about its professional trajectory and its scientific production and to inventory the collection left in the herbaria referring to the flora of Minas Gerais, analyzing where, when and with whom samples were collected. The eponymy were also rescued, tributes given by other botanists taxonomists when describing new taxa. The methodology consisted of research using private documents provided by his relatives, interviews, revision of samples in the herbariums and the construction of a database containing the records of collections deposited in Brazil and abroad herbaria. For the evaluation of the taxa described by him, specialized bibliographies were used for the family Melastomataceae and consultation of specialists. In relation to the collection left, 9063 records were found in the two main databases of virtual herbaria available in Brazil. The Brazilian herbaria with the highest number of specimens collected by Mello Barreto were BHCB (5,181), SP (1,059), RB (929) and R (443). The most representative groups were Fabaceae, Melastomataceae, Asteraceae and Rubiaceae. The years 1933, 1935 and 1937 were the ones with the most collections. The analysis of the geographical distribution indicates that all regions of the state where visited by him, but Belo Horizonte was the locality with the highest number of records, followed by Lagoa Santa and Santa Luzia. The Serra do Cipó region is also worth mentioning. The collection partnerships began after 1934, with the collaboration of 16 researchers, some from abroad. He recognized several new taxonomic entities in Melastomataceae, especially in Lavoisiera, but most of them were not efectively published. A total of 25 specific epithet was given in their honor, mostly because their samples were type material. We also highlight the participation in landscape projects with Burle-Marx in Minas Gerais, beginning in the 1940s, incorporating the use of native ornamental species. Mello Barreto left a huge scientific legacy on the flora of Minas Gerais and, for this, must be considered one of the most important and recognized botanist in the 1930 and 1940 decades.